POSSIBLE MECHANISMS OF THE DEVELOPMENT OF INSULIN RESISTANCE IN OBESITY - Поддубная, Антонина; Гончарук, Людмила; Андрущак, Маргарита; Коба, Виталина; Лысак, Иван; Маковийчук, Кристина (SWorldJournal, 2023)
Metabolic syndrome was previously associated with an increased risk of cardiovascular disease. However, research in recent decades has shown that the components of the metabolic syndrome have an effect on other systems of substances. The article provides